2020
DOI: 10.1002/1438-390x.12071
|View full text |Cite|
|
Sign up to set email alerts
|

Macrogeographic variation of a pond predator's top‐down effects in a common garden environment

Abstract: Geographic variation in species behavior and life history has been well documented in biology. Species with wide geographic distributions (i.e., across a continent) but small home ranges (i.e., <1 km2) likely experience wide variability in abiotic environments across the entirety of their range, possibly exhibiting strong local adaptation. Understanding variation across a large geographic scale is especially important when considering species that have strong ecological importance, such as keystone species. Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Larvae overwinter in ponds prior to undergoing metamorphosis in late spring to early summer. Larval diet primarily consists of zooplankton, other invertebrates, and larvae of other amphibians (Branch & Altig, 1981; Petranka & Petranka, 1980; Stemp et al, 2021). Larvae are also known to be highly aggressive and cannibalistic on conspecifics, especially if size variation among individuals exists (Mott & Maret, 2011; Smith, 1990; Walls & Blaustein, 1995).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Larvae overwinter in ponds prior to undergoing metamorphosis in late spring to early summer. Larval diet primarily consists of zooplankton, other invertebrates, and larvae of other amphibians (Branch & Altig, 1981; Petranka & Petranka, 1980; Stemp et al, 2021). Larvae are also known to be highly aggressive and cannibalistic on conspecifics, especially if size variation among individuals exists (Mott & Maret, 2011; Smith, 1990; Walls & Blaustein, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Larvae are also known to be highly aggressive and cannibalistic on conspecifics, especially if size variation among individuals exists (Mott & Maret, 2011; Smith, 1990; Walls & Blaustein, 1995). Larval A. opacum are top predators in fishless ponds, influencing both amphibian and invertebrate communities (Davenport & Chalcraft, 2012; Morin, 1995; Stemp et al, 2021; Urban, 2013). Recent evidence in South Carolina has shown that the median breeding date for A. opacum has also shifted to 15 days later than the historical median date (Todd et al, 2011), suggesting larvae would have a smaller body size in the spring and a reduced role as a top predator (Urban, 2007) unless compensatory growth occurs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraspecific trait variation can have important ecological effects, altering interactions and reshaping communities and ecosystems (Albert, 2015 ; Bolnick et al, 2011 ; Des Roches et al, 2018 ; Hairston et al, 2005 ; Harmon et al, 2009 ; Hughes et al, 2008 ; Palkovacs et al, 2012 ; Raffard et al, 2019 ). Much evidence for the community effects of intraspecific trait variation focuses on predators directly altering prey communities (Butler, 1989 ; Des Roches et al, 2013 ; Hughes et al, 2015 ; Katano, 2011 ; Matthews et al, 2016 ; Palkovacs & Post, 2009 ; Stemp et al, 2020 ; Wood et al, 2019 ) and genetic variation in foundation species (Bangert et al, 2008 ; Hays et al, 2021 ; Hughes et al, 2008 ; Whitham et al, 1999 ). However, predators of foundation species can have indirect effects on communities by altering habitat structure, both through nonconsumptive (Catalán et al, 2021 ) and consumptive effects (Hughes et al, 2015 ; Navarrete, 1996 ; Paine, 1966 ).…”
Section: Introductionmentioning
confidence: 99%